2007
DOI: 10.1111/j.1750-3841.2007.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sanitizing Fabric Wipe for Use on Food Contact Surfaces

Abstract: A sanitizer was incorporated into disposable sanitary wipes that were used to eliminate microorganisms on plastic and metal surfaces. These surfaces were inoculated with strains of Bacillus subtilis OSU 494, Enterococcus faecalis OSU 48, Escherichia coli ATCC 29181, Listeria innocua ATCC 33090, Pseudomonas aeruginosa OSU 167, Salmonella enteritidis OSU 799, Staphylococcus epidermidis OSU 838), Candida albicans ATCC 10231, and Aspergillus fumigatus ATCC 10894. These inoculated surfaces were cleaned with the wip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The effectiveness of NEW or AEW has been examined by several researchers and they have been recommended as novel food contact surface sanitizers (Izumi ; Deza and others ; Deza and others ). The use of AEW solution effectively reduced the bacterial populations on metal and plastic surfaces, as well as on disposable fabric wipes (Lee and others ,b). Handojo and others () used NEW and AEW to achieve antimicrobial effect against E. coli K‐12 and S. epidermidis inoculated onto stainless steel cutlery, ceramic plates, and drinking glasses (Table ).…”
Section: Applications Of Ewmentioning
confidence: 99%
“…The effectiveness of NEW or AEW has been examined by several researchers and they have been recommended as novel food contact surface sanitizers (Izumi ; Deza and others ; Deza and others ). The use of AEW solution effectively reduced the bacterial populations on metal and plastic surfaces, as well as on disposable fabric wipes (Lee and others ,b). Handojo and others () used NEW and AEW to achieve antimicrobial effect against E. coli K‐12 and S. epidermidis inoculated onto stainless steel cutlery, ceramic plates, and drinking glasses (Table ).…”
Section: Applications Of Ewmentioning
confidence: 99%
“…Therefore, over the range of values studied, roughness has no significant effect on the removal efficiency of bacteria by PP or Lyocell nonwoven wipes loaded with quaternary ammonium compound biocidal lotion. Lee et al [20] reported similar findings, after comparing removal from "smooth" plastic and "rough" metal surfaces, finding no significant difference (p > 0.05) in the number of E. coli and E. faecalis CFUs.…”
Section: Bacterial Removal Efficiency and The Effect Of Surface Roughnessmentioning
confidence: 60%